Gestión administrativa en Mueblería "Su Hogar" ubicado en la ciudad de Babahoyo, durante el periodo 2023. - Fajardo Moreno, Suny Juleidy (2025)
The objective of this project is to analyze the administrative management of Mueblería “Su Hogar” located in the city of Babahoyo, during the period 2023. In the business the problem lies in different failures of the administration that have repercussions in different areas, especially the commercial part; since there is no training to the sellers, nor have decisions been made to address negative situations in logistics and inventory issues. The methodology applied in this work has a qualitative approach, considering the type of descriptive research and with it the application of an interview to the furniture store manager, which allowed to collect data from a direct source to learn about the internal reality of the business and what should be improved to achieve objectives. The results showed that the main repercussions of the failures in the administration of the business are registered in the low level of sales and the lack of motivation of the employees, which leads to low labor productivity. It is concluded that the administrative management affects the productivity of the business, so it is recommended the implementation of an administrative process, in which objectives are set so that there is a basis in the daily work and more commitment of employees.